Performance and variability for yield and yield contributing characters in spring wheat (Journal of the Bangladesh Agricultural University, 2011)
The present study was conducted with twenty bread wheat genotypes at the experimental field of Bangladesh Agricultural University (BAU), Mymensingh, during the period from November 2008 to March 2009 to assess performance of the genotypes, variability, heritability and genetic advance among yield and important yield contributing characters. Considering yield per plant the genotype Peacock was the best followed by BAW-1008, Pavon-76, Mayoor, Bulbul and BAW-1004. BAW-1008 was the early maturing genotype followed by Mayoor, BAW- 861, BAW-1004 and Balaka. BAW-970, Akbar, BAW-1004, Pavon-76, BAW-861 and BAW-1006 were semi dwarf in plant height as such they were of desired type. TP-1 and Mayoor were superior for effective tillers per plant. BAW- 1004 was the best genotype for spike length and grains per spike. For 100-grain weight Bulbul, for harvest index BAW-1006 was the best. Days to 90% maturity, plant height, grains per spike, 100-grain weight and harvest index exhibited high heritability. Among them grains per spike, 100-grain weight and harvest index showed high genetic advance in percentage of mean. Keywords: Spring wheat; Variability; Heritability; Yield contributing characters DOI: 10.3329/jbau.v8i2.7924 J. Bangladesh Agril. Univ. 8(2): 195-197, 2010